3D Finite Volume Modeling of ENDE Using Electromagnetic T-Formulation. (12th June 2012) - Li, Yue; Berthiau, Gérard; Feliachi, Mouloud; Cheriet, Ahmed
Abstract : An improved method which can analyze the eddy current density in conductor materials using finite volume method is proposed on the basis of Maxwell equations and T -formulation. The algorithm is applied to solve 3D electromagnetic nondestructive evaluation (E'NDE) benchmark problems. The computing code is applied to study an Inconel 600 work piece with holes or cracks. The impedance change due to the presence of the crack is evaluated and compared with the experimental data of benchmark problems No. 1 and No. 2. The results show a good agreement between both calculated and measured data.